Online and offline social contact survey data analysis - Foo, Amanda Kar Wee. (2011)
In the recent years, the increase in the outbreak of influenza pandemic has affected the worldwide human population. Social Contact between individuals is contributory for the direct transmission spread of influenza. Thus, it is important to grasp the patterns of social contacts in a population. Surveys were randomly distributed to assess the number of social contacts for both weekdays and weekends at different locations. The studies reveal that the highest number of contact on a weekday for students is during school curriculum and for the working population is in the workplace. The weekend activities varies according to each individual preference but the locations that have the highest average number throughout the entire day are places of worship, shopping in town and nearby, market and in the swimming pool. In the event of pandemic, intervention measures should be taken in institutions, organizations, places of worship and in the swimming pool. The public should also be advised to reduce shopping and marketing activities. Studies were also done on the comparison between online and offline surveys to ensure accuracy of information provided by the respondents. The results were not of statistical significance, thus the online and offline surveys provided by the respondents were proved to be of equal importance.